Pengembangan dan peningkatan kualitas usaha kerajinan berbasis limbah kayu jati - Dewanti, F. Deru; Guniarti, Guniarti; Sulistyono, Agus; Koentjoro, Yonny; Liliek, Liliek (University of Islam Malang, 2021)
The problem is the abundance of untapped teak wood waste that has an impact on environmental pollution. The purpose of this community service activities is to develop an agro-industrial area and become a marketing platform for wood waste processing products. The service activities include: (1) programing preparation and socialization stage, (2) programing and to do exhibition assistance training, (3) monitoring and evaluation, (4) Marketing and promotion. The results obtained from processed teak waste are in the form of vehicle souvenirs such as cars, vespa, motorbikes, rickshaws, mineral water containers, fruit containers, and ashtrays which have been exhibited as superior products at the sub-district level. This program is implemented by UPN Veteran East Java together with Soerja Ngawi University and the Ngawi Food Security Agency. Activities carried out include comparative studies, mentoring, apprenticeship, procurement of tools and training for making souvenirs from waste, and marketing for groups of craftsmen. Waste processing is beneficial for the community in increasing knowledge and skills, increasing community income, and making the regional superior product of Ngawi Regency. Environmental pollution can be overcome by utilizing waste into superior products.